Silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, preparation method thereof and aqueous organic flow battery
Through the silicon hybrid microporous quaternary ammonium frame ion exchange membrane, combining the ion sieving effect of the microporous structure and the electrostatic interaction of the charged groups, it solves the problem that traditional membranes are difficult to take into account high conductivity and high selectivity, achieving more efficient ion transport and selectivity, and extending the service life of the battery.
Patent Information
- Application Number
- CN202411965838.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional polymer ion exchange membranes are difficult to take into account both high ion conductivity and high selectivity, which affects the battery's energy storage capacity and energy efficiency, and accelerates battery aging and shortens service life.
A silicon hybrid microporous quaternary ammonium frame ion exchange membrane is used to form a film with excellent cell performance through the ion sieving of the microporous structure and the electrostatic interaction of the charged groups. The positively charged three-dimensional hybrid polymer network of this membrane has a narrow pore size distribution, effectively repelling active substances and promoting the rapid transmission of charge counterions.
It significantly improves the ion selection conduction performance of the flow battery, reduces the cross-penetration of positive and negative electrode active materials, extends the battery maintenance cycle, and has better performance than commonly used commercial membranes such as SelemionAMVN and Fumasep FAA-3-PE-30.
Smart Images

Figure CN119920922A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microporous ion conduction membranes, and in particular to a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane and a preparation method thereof, and an aqueous organic liquid flow battery. Background Art
[0002] Under the background of energy revolution and dual carbon goals, large-scale energy storage technology has become a research hotspot. Different from the strong acid working conditions of all-vanadium liquid flow batteries, neutral aqueous organic liquid flow batteries use neutral NaCl solution as the supporting electrolyte. The product is safer and more environmentally friendly, with high energy conversion efficiency and long cycle life. The electrolyte is an organic molecule with the advantages of low cost, abundant sources and environmental protection. It is a new direction for the development of electrochemical energy storage. Ion exchange membrane is a key material for liquid flow batteries. It prevents the positive and negative active substances from mixing and conducts ions to form a circuit inside the battery. Its performance directly affects the performance and life of the liquid flow battery. The design paradigm of traditional polymer ion membranes relies on the structure-activity relationship of microphase separation. It is difficult to take into account both high ionic conductivity and high selectivity at the same time, which will affect the energy storage capacity and energy efficiency of the battery, and will also accelerate battery aging and shorten its service life. Therefore, it is urgent to develop new membrane materials to improve ion transport and selectivity.
[0003] Microporous framework materials (such as MOFs, COFs, CMPs) can achieve precise control of pore size and modification of pore chemical environment, promoting interaction with specific ions. However, these materials have poor solution processability and are not easy to form membranes over large areas. Silicon-hybridized microporous quaternary ammonium framework ion exchange membranes are made using a polymer sol route, which is a simple and safe process. Its microporous channels can effectively control the transport of water and ions, achieving a balance and performance breakthrough in conductivity and ion selectivity. The development of high-performance silicon-hybridized microporous quaternary ammonium framework ion exchange membranes for neutral organic flow batteries is of great research significance. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art and to provide a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane and a preparation method thereof and an aqueous organic liquid flow battery.
[0005] The present invention aims to improve the ion selective conductivity of the ion exchange membrane of the liquid flow battery, and provides a method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane. Combining the ion screening effect of the microporous structure and the electrostatic interaction of the charged groups, the membrane has excellent battery performance and is suitable for neutral aqueous organic liquid flow batteries.
[0006] The technical solution of the present invention is as follows:
[0007] The first aspect of the present invention provides a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, wherein the main structure of the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane comprises a chemical structure as shown below:
[0008]
[0009] Among them, n is 1 to 6, and x is 2 to 100.
[0010] Preferably, the raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane include tertiary amine type multi-branched siloxane monomers, and the tertiary amine type multi-branched siloxane monomers are synthesized by quaternization to have N + Center or N + Center and N + A branched multi-branched precursor, wherein the multi-branched precursor is constructed by condensation polymerization to form a branched multi-branched precursor. + A silicon-hybridized microporous quaternary ammonium framework ion exchange membrane with a three-dimensional network structure and Si as an extension point;
[0011] The chemical structure of the tertiary amine type multi-branched siloxane monomer is as follows:
[0012]
[0013] Where R is -(CH2) n -, n is 1 to 6, preferably, n is 1 to 3; R' is -CH3, -CH2CH3 or -CH2CH2CH3, preferably, R' is -CH3 or -CH2CH3.
[0014] Preferably, the raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane also include a modifier, and the tertiary amine type multi-branched siloxane monomer is synthesized by quaternization under the action of the modifier to have N + Center or N + Center and N + Multi-branched precursors of branched chains;
[0015] The modifier is at least one of methyl iodide and 3-bromopropyltrimethylammonium bromide.
[0016] Preferably, the multi-branched precursor has at least one chemical structure as shown below:
[0017]
[0018] Where R is -(CH2) n -, n is 1 to 6, preferably, n is 1 to 3; R' is -CH3, -CH2CH3 or -CH2CH2CH3, preferably, R' is -CH3 or -CH2CH3.
[0019] Preferably, the raw material for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane further includes a polymer solution, and the solute of the polymer solution is at least one of cellulose acetate, ethyl cellulose and polyvinyl pyrrolidone.
[0020] The second aspect of the present invention provides a method for preparing the above-mentioned silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, comprising the following steps:
[0021] S1, adding a tertiary amine type multi-branched siloxane monomer to a solvent, stirring evenly, and then adding a modifier to react to obtain a quaternary ammonium type multi-branched siloxane monomer;
[0022] S2, dissolving the quaternary ammonium multi-branched siloxane monomer in a solvent, adding a polymer solution, and subjecting the mixture to a polycondensation reaction to obtain a polymer sol;
[0023] S3, filtering the polymer sol to remove impurities to obtain a casting solution; subjecting the casting solution to a gelation reaction to obtain a membrane; subjecting the membrane to an ion exchange to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0024] Preferably, the step S1 specifically includes:
[0025] The tertiary amine type multi-branched siloxane monomer is dissolved in a dry solvent in an anhydrous and oxygen-free glove box environment, and a modifier is added after stirring evenly, and refluxed at 25-85° C. in the dark for 6-48 hours, and after cooling to room temperature, the solvent is removed by vacuum distillation to obtain a quaternary ammonium type multi-branched siloxane monomer;
[0026] Wherein, the molar ratio of the tertiary amine type multi-branched siloxane monomer to the modifier is 1:1-3;
[0027] The solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol dried with calcium hydride;
[0028] The molar concentration of the tertiary amine multi-branched siloxane monomer in the solvent is 0.5-1 mol / L.
[0029] Preferably, the step S2 specifically includes:
[0030] The quaternary ammonium multi-branched siloxane monomer is dissolved in a solvent, and the polymer solution, deionized water and dilute hydrochloric acid are added thereto, and the polycondensation reaction is carried out under continuous stirring at 20-40° C. for 12-48 hours to obtain a polymer sol;
[0031] Wherein, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol;
[0032] The molar concentration of the quaternary ammonium multi-branched siloxane monomer in the solvent is 0.5-1 mol / L;
[0033] The solute mass fraction of the polymer solution is 10-15%;
[0034] The molar ratio of the quaternary ammonium multi-branched siloxane monomer to the structural unit of the polymer is 1:0.5-1.5;
[0035] The molar ratio of the quaternary ammonium multi-branched siloxane monomer, deionized water and hydrogen chloride is 1:10-75:0.01-0.25;
[0036] The concentration of the dilute hydrochloric acid is 0.1-1 mol / L.
[0037] Preferably, the step S3 specifically includes:
[0038] The polymer sol is filtered to remove impurities to obtain a casting solution, and the casting solution is subjected to a gelation reaction at 25 to 80° C. for 20 to 36 hours to obtain a membrane; the membrane is peeled off, immersed in a 1 to 2 mol / L sodium chloride solution for 20 to 30 hours to perform ion exchange, and then the membrane is immersed in deionized water for 20 to 30 hours to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0039] A third aspect of the present invention provides an aqueous organic liquid flow battery, comprising the above-mentioned silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0040] The present invention has at least one of the following beneficial effects:
[0041] 1. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane of the present invention breaks through the design paradigm of the microphase separation structure of the traditional liquid flow battery diaphragm, and combines the ion screening effect of the microporous structure with the electrostatic interaction of the charged groups, which is beneficial to improving the ion selective conduction performance; the positively charged three-dimensional hybrid polymer network has a narrow pore size distribution, which effectively excludes active substances while allowing rapid transmission of charge-balanced ions.
[0042] 2. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane of the present invention can effectively reduce the cross-penetration phenomenon of positive and negative electrode active substances in aqueous organic liquid flow batteries, significantly reduce the battery capacity attenuation, extend the battery maintenance cycle, and the battery performance is better than commonly used commercial membranes such as SelemionAMVN and Fumasep FAA-3-PE-30.
[0043] 3. The present invention provides a preparation method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, which has a simple synthesis process, mild reaction conditions, no need for superacid noble metal catalysis, low equipment requirements, low raw material prices, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1The present invention provides a synthetic route and a schematic structural diagram of the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0045] Figure 2 The synthetic route and structural schematic diagram of the membrane SQA-1 prepared in Example 1.
[0046] Figure 3 This is the H-NMR spectrum of the quaternary ammonium multi-branched siloxane monomer of Example 1.
[0047] Figure 4 This is the EDS element mapping of the surface of the film SQA-1 prepared in Example 1.
[0048] Figure 5 This is the synthesis route and structural schematic diagram of the membrane SQA-2 prepared in Example 2.
[0049] Figure 6 This is the H-NMR spectrum of the quaternary ammonium multi-branched siloxane monomer of Example 2.
[0050] Figure 7 The membrane SQA-2 prepared in Example 2 was -2 The cycle performance diagram below.
[0051] Figure 8 The membrane SQA-3 prepared in Example 3 and the AMVN prepared in Comparative Example 2 were tested at 60 mA·cm -2 The cycle capacity retention rate diagram below. DETAILED DESCRIPTION
[0052] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0053] An embodiment of the present invention provides a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, wherein the main structure of the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane includes the following chemical structure:
[0054]
[0055] Among them, n is 1 to 6, and x is 2 to 100.
[0056] The typical traditional anion membrane in the prior art is a microphase separation structure, with a linear polymer main chain and a quaternary ammonium structure side chain. A small number of anion membranes use silane coupling agents such as tetraethyl silicate to crosslink the side chains. The siloxane clusters formed are dense structures and dispersed with each other, and do not play an ion screening role. Compared with the prior art, the main body of the present invention is a three-dimensional polysilane network, and the multi-rings formed by NC-Si-O are positively charged and interconnected to form through holes, and the hydrophilic quaternary ammonium unit promotes the formation of continuous hydrophilic channels. In addition, the positively charged skeleton can further repel cations in the solution, so that anions can selectively pass through.
[0057] The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane of the present invention contains a positively charged three-dimensional framework composed of polycyclic rings of quaternary ammonium, which has both Donan effect and ion screening effect, and the framework structure effectively reduces membrane swelling and increases dimensional stability. In addition, the self-assembly of quaternary ammonium branches synergistically regulates the size and charge of ion channels. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane achieves a balance between ion selection and permeation, and exhibits good battery performance when used in a neutral aqueous organic liquid flow battery system.
[0058] In some embodiments, n can be 1-5 or 2-6, preferably 2-4 or 3-5, more preferably 2-3 or 4-5, specifically 1, 2, 3, 4, 5 or 6.
[0059] In some embodiments, x can be 2 to 80, preferably 2 to 50, more preferably 2 to 10, further preferably 2 to 6 or 3 to 7 or 4 to 8, and specifically can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90 or 100, etc.
[0060] In some embodiments, the raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane include tertiary amine type multi-branched siloxane monomers, and the tertiary amine type multi-branched siloxane monomers are synthesized by quaternization to have N + Center or N + Center and N + A branched multi-branched precursor (quaternary ammonium multi-branched siloxane monomer), wherein the multi-branched precursor is constructed by polycondensation to form a + A silicon-hybridized microporous quaternary ammonium framework ion exchange membrane with a three-dimensional network structure and Si as an extension point;
[0061] The chemical structure of the tertiary amine type multi-branched siloxane monomer is as follows:
[0062]
[0063] Where R is -(CH2) n-, n is 1 to 6, preferably, n is 1 to 3; R' is -CH3, -CH2CH3 or -CH2CH2CH3, preferably, R' is -CH3 or -CH2CH3;
[0064] Preferably, the tertiary amine type multi-branched siloxane monomer is one or more of tris(triethoxysilylpropyl)amine, tris(triethoxysilylethyl)amine, tris(triethoxysilylmethyl)amine, tris(trimethoxysilylpropyl)amine, tris(trimethoxysilylethyl)amine, and tris(trimethoxysilylmethyl)amine; preferably one or two of tris(triethoxysilylpropyl)amine or tris(triethoxysilylmethyl)amine.
[0065] In some embodiments, the raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane also include a modifier, and the tertiary amine type multi-branched siloxane monomer is synthesized by quaternization under the action of the modifier to have N + Center or N + Center and N + Branched multi-branched precursor (quaternary ammonium multi-branched siloxane monomer);
[0066] The modifier is at least one of methyl iodide and 3-bromopropyltrimethylammonium bromide.
[0067] In some embodiments, the multi-branched precursor has at least one chemical structure as shown below:
[0068]
[0069] Where R is -(CH2) n -, n is 1 to 6, preferably, n is 1 to 3; R' is -CH3, -CH2CH3 or -CH2CH2CH3, preferably, R' is -CH3 or -CH2CH3.
[0070] In some embodiments, the reaction route of the tertiary amine type multi-branched siloxane monomer reacting with the modifier to form a multi-branched precursor is as follows:
[0071]
[0072] In some embodiments, the raw material for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane further includes a polymer solution, and the solute of the polymer solution is at least one of high molecular weight cellulose acetate, ethyl cellulose, and polyvinyl pyrrolidone.
[0073] The polymer can play a toughening effect. By blending the quaternary ammonium multi-branched siloxane monomer with the polymer, chemical bonds or hydrogen bonds formed between the siloxane and the polymer can improve the strength of the ion exchange membrane and avoid the problem of poor self-supporting film-forming properties of pure polysiloxane.
[0074] An embodiment of the present invention provides a method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, comprising the following steps:
[0075] S1, adding a tertiary amine type multi-branched siloxane monomer to a solvent, stirring evenly, and then adding a modifier to react to obtain a quaternary ammonium type multi-branched siloxane monomer;
[0076] S2, dissolving the quaternary ammonium multi-branched siloxane monomer in a solvent, adding a polymer solution, and subjecting the mixture to a polycondensation reaction to obtain a polymer sol;
[0077] S3, filtering the polymer sol to remove impurities to obtain a casting solution; subjecting the casting solution to a gelation reaction to obtain a membrane; subjecting the membrane to an ion exchange to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0078] The synthetic route of silicon hybrid microporous quaternary ammonium framework ion exchange membrane is as follows Figure 1 shown.
[0079] The synthesis process of the invention is simple, the reaction conditions are mild, no superacid noble metal catalysis is required, the equipment requirements are not high, the raw material price is low, and it is suitable for large-scale production.
[0080] In some embodiments, the tertiary amine multi-branched siloxane monomer is dissolved in a dry solvent in an anhydrous and oxygen-free glove box environment, and a modifier is added after stirring evenly, and refluxed at 25-85° C. in the dark for 6-48 hours, and after cooling to room temperature, the solvent is removed by vacuum distillation to obtain a quaternary ammonium multi-branched siloxane monomer;
[0081] Wherein, the molar ratio of the tertiary amine type multi-branched siloxane monomer to the modifier is 1:1-3;
[0082] The solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol dried with calcium hydride;
[0083] The molar concentration of the tertiary amine multi-branched siloxane monomer in the solvent is 0.5-1 mol / L.
[0084] In some embodiments, step S2 specifically includes:
[0085] The quaternary ammonium multi-branched siloxane monomer is dissolved in a solvent, and the polymer solution, deionized water and dilute hydrochloric acid are added thereto, and the polycondensation reaction is carried out under continuous stirring at 20-40° C. for 12-48 hours to obtain a polymer sol;
[0086] Wherein, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol;
[0087] The molar concentration of the quaternary ammonium multi-branched siloxane monomer in the solvent is 0.5-1 mol / L;
[0088] The solute mass fraction of the polymer solution is 10-15%;
[0089] The molar ratio of the quaternary ammonium multi-branched siloxane monomer to the structural unit of the polymer is 1:0.5-1.5;
[0090] The molar ratio of the quaternary ammonium multi-branched siloxane monomer, deionized water and hydrogen chloride is 1:10-75:0.01-0.25;
[0091] The concentration of the dilute hydrochloric acid is 0.1-1 mol / L.
[0092] In some embodiments, step S3 specifically includes:
[0093] The polymer sol is filtered to remove impurities to obtain a casting solution, and the casting solution is subjected to a gelation reaction at 25 to 80° C. for 20 to 36 hours to obtain a membrane; the membrane is peeled off, immersed in a 1 to 2 mol / L sodium chloride solution for 20 to 30 hours to perform ion exchange, and then the membrane is immersed in deionized water for 20 to 30 hours to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0094] Another embodiment of the present invention provides an aqueous organic flow battery, comprising the above-mentioned silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
[0095] The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane of the present invention can effectively reduce the cross-permeation phenomenon of positive and negative electrode active substances in aqueous organic liquid flow batteries, significantly reduce the battery capacity attenuation, extend the battery maintenance cycle, and the battery performance is better than commonly used commercial membranes such as SelemionAMVN and Fumasep FAA-3-PE-30.
[0096] In some embodiments, the aqueous organic flow battery is any one or more of bipyridine, TEMPO, and ferrocene.
[0097] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0098] The main raw material sources in the embodiments of the present invention are: tris(triethoxysilylpropyl)amine (GELEST), tris(triethoxysilylmethyl)amine (GELEST), cellulose acetate (Sigma-Aldrich), ethyl cellulose (Sigma-Aldrich), polyvinyl pyrrolidone (Sigma-Aldrich), iodomethane (Annaiji), and 3-bromopropyltrimethylammonium bromide (Aladdin).
[0099] Example 1
[0100] A method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, the reaction route is as follows Figure 2 As shown, the following steps are included:
[0101] (1) Synthesis of quaternary ammonium precursor: In an anhydrous and oxygen-free N2 glove box, 1 mL of tri(triethoxysilylpropyl)amine was added to a flask, and 2 mL of ethanol dried over CaH2 was added. After magnetic stirring and mixing, 289 μL of iodomethane was added. The mixture was refluxed at 32°C in the dark for 48 h. After cooling to room temperature, the solvent was removed by vacuum distillation to obtain a quaternary ammonium multi-branched siloxane monomer for standby use.
[0102] (2) Synthesis of polymer sol: 1.19 g of quaternary ammonium multi-branched siloxane monomer was weighed and dissolved in 2 mL of N,N-dimethylacetamide, and 5 g of 10% by mass cellulose acetate N,N-dimethylacetamide solution was added. After stirring and mixing evenly, 0.6 mL of 0.1 mol / L dilute hydrochloric acid was slowly added. The mixture was continuously stirred at 30° C. for 48 h to carry out polycondensation reaction to obtain a polymer sol.
[0103] (3) Preparation of silicon-hybridized microporous quaternary ammonium framework ion exchange membrane: The polymer sol was cast in an ultra-flat quartz dish and subjected to gelation reaction at 60°C for 24 h. After drying, the membrane was peeled off and immersed in 1.5 mol / L sodium chloride solution for 24 h to carry out sufficient ion exchange. The membrane was then immersed in deionized water for 24 h to remove excess sodium chloride. The obtained silicon-hybridized microporous quaternary ammonium framework ion exchange membrane was recorded as SQA-1.
[0104] (4) Battery performance test: The test was conducted using the Blue Electric Battery Test System. A film sample (6 cm × 7 cm) was cut and sandwiched between graphite felts (9 cm 2 The positive electrode electrolyte is a 0.2 mol / L aqueous solution of nitroxyl piperidinol, the negative electrode electrolyte is a 0.2 mol / L aqueous solution of methyl viologen, and 3 mol / L NaCl is added to each electrode as a supporting electrolyte. The voltage range of 1.5-0.55 V is 60 mA cm -2 The single cell is cross-current charged and discharged at a current density of .
[0105] Example 2
[0106] A method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, the reaction route is as follows Figure 3 As shown, the following steps are included:
[0107] (1) Synthesis of quaternary ammonium precursor: In an anhydrous and oxygen-free N2 glove box, 1.2 mL of tri(triethoxysilylpropyl)amine was added to a flask, and 3.6 mL of n-butanol dried with CaH2 was added. After being mixed evenly by magnetic stirring, 0.48 g of 3-bromopropyltrimethylammonium bromide was added. The mixture was refluxed at 80°C for 12 h. After being cooled to room temperature, the solvent was removed by vacuum distillation to obtain a quaternary ammonium multi-branched siloxane monomer for standby use.
[0108] (2) Synthesis of polymer sol: 1.65 g of quaternary ammonium multi-branched siloxane monomer was weighed and dissolved in 3 mL of ethanol, 4 g of 15% ethyl cellulose ethanol solution was added, and after stirring and mixing evenly, 0.4 mL of 1 mol / L dilute hydrochloric acid was slowly added, and the mixture was continuously stirred at 30° C. for 24 h to carry out polycondensation reaction to obtain a polymer sol;
[0109] (3) Preparation of silicon-hybridized microporous quaternary ammonium framework ion exchange membrane: The polymer sol was cast in an ultra-flat quartz dish and subjected to gelation reaction at 30°C for 36 h. After drying, the membrane was peeled off and immersed in 1.5 mol / L sodium chloride solution for 24 h to carry out sufficient ion exchange. The membrane was then immersed in deionized water for 24 h to remove excess sodium chloride. The obtained silicon-hybridized microporous quaternary ammonium framework ion exchange membrane was recorded as SQA-2.
[0110] (4) Battery performance test: same as in Example 1.
[0111] Example 3
[0112] A method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane comprises the following steps:
[0113] (1) Synthesis of quaternary ammonium precursor: In an anhydrous and oxygen-free N2 glove box, 1.5 mL of tri(triethoxysilylmethyl)amine was added to a flask, and 4.2 mL of n-butanol dried with CaH2 was added. After being mixed evenly by magnetic stirring, 0.61 g of 3-bromopropyltrimethylammonium bromide was added. The mixture was refluxed at 80°C for 12 h. After being cooled to room temperature, the solvent was removed by vacuum distillation to obtain a quaternary ammonium multi-branched siloxane monomer for standby use.
[0114] (2) Synthesis of polymer sol: 2.07 g of quaternary ammonium multi-branched siloxane monomer was weighed and dissolved in 3 mL of ethanol, 3 g of 10% ethyl cellulose ethanol solution was added, and after stirring and mixing evenly, 1.5 mL of 0.1 mol / L dilute hydrochloric acid was slowly added, and the mixture was continuously stirred at 30° C. for 20 h to carry out polycondensation reaction to obtain a polymer sol;
[0115] (3) Preparation of silicon-hybridized microporous quaternary ammonium framework ion exchange membrane: The polymer sol was cast in an ultra-flat quartz dish and subjected to gelation reaction at 30°C for 36 h. After drying, the membrane was peeled off and immersed in 1.5 mol / L sodium chloride solution for 24 h to carry out sufficient ion exchange. The membrane was then immersed in deionized water for 24 h to remove excess sodium chloride. The obtained silicon-hybridized microporous quaternary ammonium framework ion exchange membrane was recorded as SQA-3.
[0116] (4) Battery performance test: same as in Example 1.
[0117] Example 4
[0118] A method for preparing a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane comprises the following steps:
[0119] (1) Synthesis of quaternary ammonium precursor: In an anhydrous and oxygen-free N2 glove box, 1 mL of tri(triethoxysilylpropyl)amine was added to a flask, and 2.5 mL of N,N-dimethylacetamide dried with CaH2 was added. After magnetic stirring and mixing, 193 μL of iodomethane was added. The mixture was refluxed at 40°C in the dark for 24 h. After cooling to room temperature, the solvent was removed by vacuum distillation to obtain a quaternary ammonium multi-branched siloxane monomer for standby use.
[0120] (2) Synthesis of polymer sol: 1.19 g of quaternary ammonium multi-branched siloxane monomer was weighed and dissolved in 2.5 mL of N,N-dimethylacetamide, and 2.5 g of 10% polyvinyl pyrrolidone in N,N-dimethylacetamide solution was added. After stirring and mixing evenly, 2 mL of 0.1 mol / L dilute hydrochloric acid was slowly added. The mixture was continuously stirred at 30° C. for 20 h to carry out polycondensation reaction to obtain a polymer sol.
[0121] (3) Preparation of silicon-hybridized microporous quaternary ammonium framework ion exchange membrane: The polymer sol was cast in an ultra-flat quartz dish and subjected to gelation reaction at 80°C for 20 h. After drying, the membrane was peeled off and immersed in 1.5 mol / L sodium chloride solution for 24 h to carry out sufficient ion exchange. The membrane was then immersed in deionized water for 24 h to remove excess sodium chloride. The obtained silicon-hybridized microporous quaternary ammonium framework ion exchange membrane was recorded as SQA-4.
[0122] (4) Battery performance test: same as in Example 1.
[0123] Comparative Example 1
[0124] A piece of commercial membrane FAA-3-PE-30 produced by Fumatech Company of Germany was cut and immersed in 1.5 mol / L sodium chloride solution for 24 h to achieve sufficient ion exchange. The membrane was then immersed in deionized water for 24 h to remove excess sodium chloride. Battery performance test: the same as in Example 1.
[0125] Comparative Example 2
[0126] A piece of commercial membrane AMVN produced by Asahi Glass Co., Ltd. was cut and immersed in a 1.5 mol / L sodium chloride solution for 24 hours to achieve sufficient ion exchange. The membrane was then immersed in deionized water for 24 hours to remove excess sodium chloride. Battery performance test: the same as in Example 1.
[0127] Comparative Example 3
[0128] (1) Weigh 0.8 mL of tetraethoxysilane monomer and dissolve it in 2 mL of N,N-dimethylacetamide solution, add 5 g of 10% by mass cellulose acetate N,N-dimethylacetamide solution, stir and mix evenly, then slowly add 0.6 mL of 0.1 mol / L dilute hydrochloric acid, and continue stirring at 30° C. for 48 hours to perform polycondensation reaction to obtain a polymer sol;
[0129] (2) The polymerized sol was cast in an ultra-flat quartz dish and subjected to gelation reaction at 60°C for 24 hours. After drying, the membrane was peeled off and immersed in a 1.5 mol / L sodium chloride solution for 24 hours to achieve sufficient ion exchange. The membrane was then immersed in deionized water for 24 hours to remove excess sodium chloride.
[0130] (3) Battery performance test: same as in Example 1.
[0131] The membrane prepared in this way cannot be used for battery charging and discharging because the densified structure formed by tetraethoxysilane and cellulose acetate makes the resistance too large.
[0132] Comparative Example 4
[0133] The difference from Example 1 is that in step (2), "5 g of 10% by mass cellulose acetate N,N-dimethylacetamide solution" is not added; the rest is the same as Example 1.
[0134] The film thus prepared was more brittle than that in Example 1 and was difficult to assemble into a battery.
[0135] Test results and analysis:
[0136] Figure 2 Shown is the synthesis route and structural schematic diagram of the membrane SQA-1 prepared in Example 1, Figure 5 The synthetic route and structural schematic diagram of the membrane SQA-2 prepared in Example 2. The ion exchange membranes prepared in Examples 1 and 2 self-assembled into a porous three-dimensional skeleton through positively charged polycyclic rings connected by NC-Si-O. The hydrophilicity of quaternary ammonium promotes the formation of continuous water channels. While achieving size screening, the positively charged skeleton can further repel cations in the solution, thereby allowing anions to selectively pass through.
[0137] Figure 3is the nuclear magnetic hydrogen spectrum of the quaternary ammonium multi-branched siloxane monomer of Example 1, Figure 6 This is the H-NMR spectrum of the quaternary ammonium multi-branched siloxane monomer of Example 2, indicating the synthesis of the multi-branched precursor.
[0138] Figure 4 The EDS element mapping diagram of the surface of the film SQA-1 prepared in Example 1 shows the uniform distribution of N, C, Si, O, and Cl elements. From the SEM photo, it can be seen that the film surface is intact and has no defects, proving the successful preparation of the film SQA-1.
[0139] Figure 7 The membrane SQA-2 prepared in Example 2 was -2 The cycling performance diagram below. During 300 battery charge and discharge cycles, CE, VE, and EE remained stable, indicating that the membrane has excellent cycling stability.
[0140] Figure 8 The membrane SQA-3 prepared in Example 3 and the AMVN prepared in Comparative Example 2 were tested at 60 mA·cm -2 The cycle capacity retention rate diagram under . After 300 battery charge and discharge cycles, compared with the commercial membrane AMVN, the battery assembled with the membrane SQA-3 prepared in Example 3 has lower electrode active material attenuation, which shows that the silicon-hybridized microporous quaternary ammonium framework structure has excellent selectivity and can effectively prevent the cross-penetration of active substances.
[0141] The performance comparison table of the ion exchange membranes of Examples 1-4 and Comparative Examples 1-2 is shown in Table 1 below.
[0142] Table 1 The membranes of Examples 1-4 and Comparative Examples 1-2 at 60 mA·cm -2 Battery performance comparison table below
[0143] Coulombic efficiency % Voltage efficiency % Energy efficiency % Example 1 99.49 81.17 80.76 Example 2 99.66 84.72 84.43 Example 3 99.87 80.06 79.96 Example 4 99.33 85.42 84.85 Comparative Example 1 98.68 55.64 54.91 Comparative Example 2 99.54 70.68 70.35
[0144] It can be seen from the above performance comparison table of the ion exchange membrane of the present invention that the aqueous organic liquid flow battery assembled with the ion exchange membrane disclosed in the embodiment of the present invention shows good battery efficiency and has advantages in the application of aqueous organic liquid flow batteries.
[0145] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silicon-hybridized microporous quaternary ammonium framework ion exchange membrane, characterized in that: The main structure of the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane includes the chemical structure shown below: Among them, n is 1 to 6, and x is 2 to 100.
2. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane according to claim 1, characterized in that: The raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane include tertiary amine type multi-branched siloxane monomers, and the tertiary amine type multi-branched siloxane monomers are synthesized by quaternization to have N + Center or N + Center and N + A branched multi-branched precursor, wherein the multi-branched precursor is constructed by condensation polymerization to form a branched multi-branched precursor. + A silicon-hybridized microporous quaternary ammonium framework ion exchange membrane with a three-dimensional network structure and Si as an extension point; The chemical structure of the tertiary amine type multi-branched siloxane monomer is as follows: Where R is -(CH2) n -, n is 1 to 6; R' is -CH3, -CH2CH3 or -CH2CH2CH3.
3. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane according to claim 2, characterized in that: The raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane also include a modifier, and the tertiary amine type multi-branched siloxane monomer is synthesized by quaternization under the action of the modifier to have N + Center or N + Center and N + Multi-branched precursors of branched chains; The modifier is at least one of methyl iodide and 3-bromopropyltrimethylammonium bromide.
4. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane according to claim 2, characterized in that: The multi-branched precursor has at least one chemical structure as shown below: Where R is -(CH2) n -, n is 1 to 6; R' is -CH3, -CH2CH3 or -CH2CH2CH3.
5. The silicon-hybridized microporous quaternary ammonium framework ion exchange membrane according to claim 2, characterized in that: The raw materials for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane also include a polymer solution, and the solute of the polymer solution is at least one of cellulose acetate, ethyl cellulose, and polyvinyl pyrrolidone.
6. The method for preparing the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, adding a tertiary amine type multi-branched siloxane monomer to a solvent, stirring evenly, and then adding a modifier to react to obtain a quaternary ammonium type multi-branched siloxane monomer; S2, dissolving the quaternary ammonium multi-branched siloxane monomer in a solvent, adding a polymer solution, and subjecting the mixture to a polycondensation reaction to obtain a polymer sol; S3, filtering the polymer sol to remove impurities to obtain a casting solution; subjecting the casting solution to a gelation reaction to obtain a membrane; subjecting the membrane to an ion exchange to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
7. The preparation method according to claim 6, characterized in that: The step S1 specifically includes: The tertiary amine type multi-branched siloxane monomer is dissolved in a dry solvent in an anhydrous and oxygen-free glove box environment, and a modifier is added after stirring evenly, and refluxed at 25-85° C. in the dark for 6-48 hours, and after cooling to room temperature, the solvent is removed by vacuum distillation to obtain a quaternary ammonium type multi-branched siloxane monomer; Wherein, the molar ratio of the tertiary amine type multi-branched siloxane monomer to the modifier is 1:1-3; The solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol dried with calcium hydride; The molar concentration of the tertiary amine multi-branched siloxane monomer in the solvent is 0.5-1 mol / L.
8. The preparation method according to claim 6, characterized in that: The step S2 specifically includes: The quaternary ammonium multi-branched siloxane monomer is dissolved in a solvent, and the polymer solution, deionized water and dilute hydrochloric acid are added thereto, and the polycondensation reaction is carried out under continuous stirring at 20-40° C. for 12-48 hours to obtain a polymer sol; Wherein, the solvent is one or more of dimethyl sulfoxide, N,N-dimethylacetamide, ethanol, and n-butanol; The molar concentration of the quaternary ammonium multi-branched siloxane monomer in the solvent is 0.5-1 mol / L; The solute mass fraction of the polymer solution is 10-15%; The molar ratio of the quaternary ammonium multi-branched siloxane monomer to the structural unit of the polymer is 1:0.5-1.5; The molar ratio of the quaternary ammonium multi-branched siloxane monomer, deionized water and hydrogen chloride is 1:10-75:0.01-0.25; The concentration of the dilute hydrochloric acid is 0.1-1 mol / L.
9. The preparation method according to claim 6, characterized in that: The step S3 specifically includes: The polymer sol is filtered to remove impurities to obtain a casting solution, and the casting solution is subjected to a gelation reaction at 25 to 80° C. for 20 to 36 hours to obtain a membrane; the membrane is peeled off, immersed in a 1 to 2 mol / L sodium chloride solution for 20 to 30 hours to perform ion exchange, and then the membrane is immersed in deionized water for 20 to 30 hours to obtain a silicon-hybridized microporous quaternary ammonium framework ion exchange membrane.
10. An aqueous organic liquid flow battery, characterized in that: The invention comprises the silicon-hybridized microporous quaternary ammonium framework ion exchange membrane as described in any one of claims 1 to 5.